Consecuencias del distanciamiento social a causa de la Covid-19 en el empleo y el mercado laboral peruano: Estadísticas y retos jurídico-normativos - Egúsquiza Palacín, Betty; Félix Córdova, Fernando Segundo (Pontificia Universidad Católica del Perú, 2023)
The Peruvian labor market was hit hard in 2020, the most critical year of the pandemic due to Covid-19. Although it seems that everything has recovered in 2021, in reality, the structural problems have been accentuated: greater informality of employment, increased predominance of fixed-term contracts and specific labor schemes, such as outsourced work and teleworking, which raise assumptions that in the new post-Covid context had not been discussed. On this occasion, we will focus on the employment and labor situation in the country in the pe-riod 2012-2021, showing that the state of affairs was already worrying and that the pandemic only aggravated the problem of the high informality of employment and the widespread use of fixed-term labor contracting, at the same time it opened the horizon of teleworking and once again brings to debate labor outsourcing, identifying some normative gaps that could constitute a whole development for a better and efficient labor regulation and institutionalism, besides calling attention to the urgent need for economic and active employment policies to overcome this reality.

El mercado de trabajo peruano fue golpeado fuertemente en el 2020, el año más crítico de la pandemia a causa de la Covid-19. Aunque parece que todo se ha recuperado en el 2021, en realidad, los problemas estructurales se han acentuado: mayor informalidad del empleo, predominancia acrecentada de la contratación a plazo fijo y esquemas específicos de laboralidad, como el trabajo tercerizado y el teletrabajo, que plantean supuestos que en el nuevo contexto post-covid no se habían discutido. En esta ocasión nos abocamos a exponer la situación del empleo y del trabajo en el país en el periodo 2012-2021, mostrando que ya el estado de cosas era preocupante y que la pandemia solo agudizó el problema de la alta informalidad del empleo y el uso ampliamente extendido de la contratación laboral a plazo fijo, a la par que aperturó el horizonte del teletrabajo y nuevamente trae a debate a la tercerización laboral, identificando algunos vacíos normativos que podrían constituir todo un desarrollo para una mejor y eficiente regulación e institucionalidad laboral, además de llamar la atención en relación a la urgente necesidad de políticas económicas y activas de empleo para superar esta realidad.
Consequences of social distancing caused by Covid-19 on employment and the Peruvian labor market: Statistics and legal-normative challenges
Keywords: Informality of employment; Wage earners; Salary; Unemployment intermediation; Outsourcing and teleworking; Informalidad del empleo; Asalariados; Remuneración; Desempleo; Intermediación; Tercerización; Teletrabajo; https://purl.org/pe-repo/ocde/ford#5.05.00